The Effectiveness of Interactive Learning Multimedia with a Contextual Approach to Student’s Understanding Mathematical Concepts - Vianida Etyarisky; Marsigit Marsigit (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to determine the effectiveness of the use of interactive learning multimedia products on the understanding of mathematical concepts, especially the angle measurement material for fourth grade elementary school students. This study used a quasi-experimental research design with a nonequivalent comparation-group design. The data collection technique used was a written test technique involving 60 students. The research data were tested using the t-test. The results showed that the use of interactive multimedia learning had a positive effect on the understanding of mathematical concepts, especially the angle measurement material for fourth grade elementary school students. The t-test results show a significance value of ˂ 0.05 so that Ho is rejected and Ha is accepted, which means that the use of interactive multimedia learning with a contextual approach is effective in improving students' conceptual understanding.